تزاوج اللغة الامازيغية بغيرها من اللغات في الممارسة والتنوع اللغوي في الجزائر: The intermingling of Amazigh and other languages in practice and linguistic diversity in Algeria - قاسيمي امال (Maalim, 2021)
The problem of multilingualism, intersectionality and linguistic intermarriage is something that many countries know, including Algeria, which lives in a society that uses three languages, namely Arabic, Amazigh and French, so that these languages are affected by each other, where the individual is using an Arabic or French vocabulary in Amazigh, which we will seek to discuss in the content of this paper, with the reasons for this overlap and the implications for this language.